Relative importance of factors affecting construction hazards in the design phase - Hosseinian, Seyyed Shahab (2013)
Identifying the root causes of construction accidents has indicated that not only contractors but designers and architectures are capable of influencing construction workers safety. The aim of this study is to investigate and prioritize factors affecting construction hazards in the design phase. To achieve the aim of this study, a questionnaire survey was distributed among respondents randomly selected from construction sites within Malaysia. Relative Importance Index method was used to prioritize factors in order of level of effect on construction hazards. The results indicated that Lack of designers safety knowledge, Lack of designers knowledge about construction processes and Late involvement of constructors in the design process have the highest level of effect while Lack of safety organizations which evaluates the safety level of design and Few application of components' prefabrication have the lowest level of effect on hazards in the design phase of construction projects.